Homens e imagens no Ocidente Medieval: uma proposta de material didático para o ensino de História Medieval na educação básica - Netto, Eduardo Revelante (2022)
This work aims to present a proposal for a teaching material and a teaching methodology for Medieval History in Basic Education. It is an activity that aims to deepen knowledge about the medieval period, with the focus of the pedagogical activity on the cult of religious images and the resulting social interactions. The aim is that with the study of textual and imagery sources about the religiosity of medieval Latin Christianity, students understand the complexity of social relations, heterogeneity, cultural richness, and the countless stories that make up this historical period. As part of the pedagogical strategy, concomitantly with the medieval study, students will study the cult of religious images in the municipality of Caibaté, the objective is to investigate if there are medieval reminiscences in the local culture. The teaching methodology to be used follows the assumptions of active methodologies, the pedagogy of projects, which instigates the protagonism of the students. The final task consists in the creation, by the students, of infographics about the cult of religious images in the Middle Ages and in Caibaté.